O VOTO NO DIREITO BRASILEIRO: HISTÓRIA, PROBLEMAS E PROPOSTAS DE MUDANÇA (Revista Direito em Debate, 2019)
The present work discusses the electoral Brazilian system within the scope of Democratic Rule of Law, as well as the compulsory vote inside this system, raising hypotheses to be answered during the course of the research. The research method used is qualitative, to synthesize the information and conclusions previously quoted. At first, it takes a historical study of electoral systems and vote as well as its origins, foundations, purposes, limits and current concept. Another issue that will be addressed is the comparative law between other existent electoral systems. In the end, the work will be completed in the search for answers to the questions raised, through the final considerations.
Keywords: Electoral Law. Vote Required. Electoral Systems. Popular Sovereignty. Citizenship.